Finite-Dimensional Nonlocal Reductions of the Inverse Korteweg–de Vries Dynamical System - Vorobyova, O. V.; Pritula, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We study finite-dimensional Moser-type reductions for the inverse nonlinear Korteweg–de Vries dynamical system and the Liouville integrability of these reductions in quadratures.